Cr (III)-Doped Bentonite: Synthesis, Characterization and Application for Phenol Removal - Purwaningrum, Widia; Vilantina, Vilantina; Rizki, Widya Twiny; Desnelli, Desnelli; Hariani, Poedji Loekitowati; Said, Muhammad (Makara Journal of Science, 2021)
Study of doping process of metal oxide Cr(III) onto bentonite for phenol removal has been done. The purpose of this study was to increase the capacity and effectiveness of bentonite adsorption.The doped bentonite was characterized using XRD, SEM-EDX and FT-IR spectrophotometer analysis. XRD characterization result showed an angle shift (2θ) characteristic at1.609°. The SEM-EDX characterization result showed that bentonite as control have a more gaps than Cr(III)-doped bentonite. Based on EDX result, the Al element decreased from 7.53% to 3.76%, Si from 19.84% to 10.23% and appeared Cr element 2.06%, The FT-IR characterization result showed no significant friction in the spectrum so it can be identified as physical adsorption. The adsorption of phenol was applied at pHpzc, which for bentonite as control was applied at pH 4 and Cr(III)- doped bentonite was applied at pH 8. The phenol adsorption rate fitted to pseudo-second-order and it was found that the equilibrium data was best followed by Freundlich isotherm model, the amount of adsorption rate constant (k) and adsorption capacity (Qe) was 0.0024 g.mg-1min-1 and 16.95 mg/g. The Enthalpy (ΔH) and entropy (ΔS) values decrease with increasing phenol concentration and the positive free energy value was indicated that the proccess was nonspontaneous because there has been an equilibrium state. Based on the adsorption result, it can be concluded that the doping method can produce better bentonite performance to adsorb phenol.